Microarray based transcriptome profile data of ∆lon and ∆lon rpoB12 strains of Escherichia coli - Shanmugaraja Meenakshi; M. Hussain Munavar (Data in Brief, 2018)
The data presented in this article shows the microarray based transcriptome profiles of ∆lon and ∆lon rpoB12 strains of Escherichia coli. The rif mutation namely, rpoB12 was isolated spontaneously in the background of ∆lon strain (over-produces colanic acid capsular polysaccharide) as a suppressor for over-production of colanic acid capsular polysaccharide (Meenakshi and Munavar, 2015) [1]. The E. coli strains were grown in LB medium at 30 °C overnight in duplicates. Total RNA from each samples were isolated and microarray based transcriptome profiles were studied and compared. The detailed methodology and data are given in this article. The interpretation of these data are discussed in the research article, “Evidence for Up and Down Regulation of 450 genes by rpoB12 (rif) Mutation and their Implications in Complexity of Transcription Modulation in Escherichia coli” (Meenakshi and Munavar, 2018) [2]. Keywords: ∆lon, rpoB12, Capsule, Biofilm, Motility, Stress response